Daniel Webster - Allen, Robert; Nang ChanYeema (Milford, MI USA Mott Media, Inc., 1989)
Traces the life of the orator and statesman who served as congressman, senator, and Secretary of State and supported the Compromise of 1850 in hopes of saving the Union.
Keywords: Biography